Identification and characterization of linear B-cell epitopes on African swine fever virus H171R protein - Cheng Xin; Zhuting Chen; Jingming Zhou; Yumei Chen; Yankai Liu; Hongliang Liu; Chao Liang; Xifang Zhu; Yanhua Qi; Gaiping Zhang; Aiping Wang (Microbiology Spectrum)
ABSTRACT African swine fever virus (ASFV) is a highly contagious and often fatal pathogen that poses a significant threat to the swine industry worldwide. The H171R protein, a structural component of ASFV, plays crucial roles in viral assembly, host cell entry, and modulation of the host immune response. This study aimed to comprehensively characterize the linear B-cell epitopes on the H171R protein to facilitate the development of diagnostic tools and subunit vaccines against ASFV. A combined approach involving bioinformatics analysis and experimental techniques was employed. The recombinant H171R protein was expressed and purified, and specific monoclonal antibodies were generated through immunization and hybridoma technology. Systematic epitope mapping using overlapping peptide fragments and alanine-scanning mutagenesis revealed four minimal linear epitopes: 84HPLLPYQQSSDEQP97, 93SDEQPMMPYQQPPG106, 111PYEQIYHKKHASQQ124, and 129LNDYYQHILALGDED143. The identified epitopes exhibited strong immunogenicity, as demonstrated by their reactivity with ASFV-positive swine sera. Critical amino acid residues within each epitope were identified through mutational analysis. Structural modeling and visualization of the H171R protein provided insights into the spatial distribution and accessibility of the epitope regions. These findings contribute to a better understanding of the H171R protein’s antigenic properties and lay the foundation for developing effective diagnostic assays and subunit vaccines against African swine fever.IMPORTANCEAfrican swine fever virus (ASFV) poses a severe threat to the global swine industry. This study characterizes linear B-cell epitopes on the crucial ASFV H171R protein, facilitating the development of improved diagnostics and subunit vaccines. Four immunogenic epitopes were identified, offering valuable information for designing sensitive diagnostic assays and potential subunit vaccine candidates. By advancing the understanding of H171R’s antigenic landscape, this research contributes to controlling ASFV’s devastating impacts, safeguarding the swine industry, and ensuring food security.